Promosi Pentingnya Konsumsi Tablet Tambah Darah sebagai Preventif Anemia pada Remaja Putri - wijayati, wahyu (STIKES dan AKZI Karya Husada Kediri, 2024)
The crucial anemia is anticipated primarily in adolescent girls; As is known, anemia status in adolescents is influenced by food availability, which is supported by adequate food security. The availability of sufficient food can influence nutritional consumption in adolescent girls. Adolescent health can be improved by preventing anemia through consuming Blood Supplement Tablets. One of the health promotion efforts related to promoting the importance of consuming Blood Supplement Tablets as a preventative for anemia in young women can be through counseling about preventing anemia at RSIA Nirmala, Kediri City, East Java Province; by face to face, to provide counseling to young women, including understanding anemia, causes of anemia, symptoms of anemia, impacts of anemia and management of anemia. The auxiliary media used in counseling is leaflets. The time for implementing health promotion/counseling activities regarding preventing anemia in adolescent girls at RSIA Nirmala, Kediri City, East Java Province, is from May 10 to July 4 2024 with stages of planning, implementation, mentoring, and evaluation for 8 adolescent girls. The results of the activity evaluation showed that there was an increase in the knowledge of young women before and after providing counseling and all young women were enthusiastic about participating in the counseling as demonstrated by the activeness of all young women in the question and answer session; So it can be said that health promotion activities through education about the importance of consuming Blood Additive Tablets as a preventative for anemia in adolescent girls can be effective in increasing knowledge among teenage girls at RSIA Nirmala, Kediri City, East Java Province.